Asmaul Husna web-based system: acquainting the 99 names of Allah / Arifah Fasha Rosmani and Nurul Amanni Ahmad Shuhaimi - Rosmani, Arifah Fasha; Ahmad Shuhaimi, Nurul Amanni (Universiti Teknologi MARA, Perlis, 2022)
Web-based systems have had a significant impact on computer and communication technology advancement. Websites are still prevalent in a variety of practices after a long time. As a result, an Islamic learning-oriented website concentrating on Asmaul Husna was formed. This project was created as the topic still requires an engaging and comprehensive informal learning method to fill the need. The website was designed using a Waterfall model-based system development life-cycle methodology. According to the testing results, this website has aided users in learning their topic more openly and at their leisure. By using this website, more people would be able to profit from learning about the subject in their daily lives.